From Social Media to E-Commerce: How TikTok Live and Sales Promotions Shape User Purchase Decisions - Lathifa Camelia Putri; Muhammad Thoyib Amali; Mufid Salim (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2026)
The rise of digital transformation has positioned social media as a key driver of e-commerce growth in Indonesia, with TikTok Shop emerging as a leading platform through its live features and promotional campaigns. This study examines the impact of TikTok Live exposure and sales promotions on user purchase decisions, using the Elaboration Likelihood Model (ELM) as a theoretical framework, in which the central and peripheral routes of persuasion play distinct roles in the consumer decision-making process. This study employed a quantitative approach by surveying 160 active TikTok users who had previously purchased on TikTok Shop. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. Findings reveal that both TikTok Live exposure and sales promotions positively and significantly influence purchase decisions, with sales promotions exhibiting a stronger effect. This study emphasizes the importance of combining informative live content with appealing promotional strategies to strengthen consumer engagement and drive sales. Future research is recommended to focus on specific brands and to incorporate additional variables, such as marketing content quality, viral marketing, online trust, or impulsive buying behavior.